2001
DOI: 10.1046/j.1360-0443.2001.961474.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive biases and addiction: an evolution in theory and method

Abstract: An evolution in theoretical models and methodological paradigms for investigating cognitive biases in the addictions is discussed. Anomalies in traditional cognitive perspectives, and problems with the self-report methods which underpin them, are highlighted. An emergent body of cognitive research, contextualized within the principles and paradigms of cognitive neuropsychology rather than social learning theory, is presented which, it is argued, addresses these anomalies and problems. Evidence is presented tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 55 publications
7
85
1
5
Order By: Relevance
“…Measures of reflection impulsivity -the tendency to gather and evaluate information before making a decision -also appears to address distinct psychological functions of importance of substance misuse (Clark et al, 2006;Morgan, 1998;Morgan et al, 2002;. Furthermore, studies have demonstrated the association of cognitive bias to drug cues and negative affect to drug use behaviors in patients with SUD using modified Stroop tasks (Bolla et al, 2004;Goldstein et al, 2007; see also Cox et al, 2006;McCusker, 2001, for a conceptual overview). As imaging data are accumulated with these paradigms, a synthesis of these results would be warranted in the future.…”
Section: General Summarymentioning
confidence: 99%
“…Measures of reflection impulsivity -the tendency to gather and evaluate information before making a decision -also appears to address distinct psychological functions of importance of substance misuse (Clark et al, 2006;Morgan, 1998;Morgan et al, 2002;. Furthermore, studies have demonstrated the association of cognitive bias to drug cues and negative affect to drug use behaviors in patients with SUD using modified Stroop tasks (Bolla et al, 2004;Goldstein et al, 2007; see also Cox et al, 2006;McCusker, 2001, for a conceptual overview). As imaging data are accumulated with these paradigms, a synthesis of these results would be warranted in the future.…”
Section: General Summarymentioning
confidence: 99%
“…Specifically, in samples of participants in treatment for problematic substance use, the number of negative expectancies related to substances was not significantly associated with relapse. Using tests of implicit processes, researchers found that though individuals high on substance use reported more negative expectancies than controls, their positive expectancies were accessed faster than their negative expectancies (McCusker, 2001(McCusker, , 2006. Negative expectancies related to substances, in those high on substance use, were more slowly accessed through deliberation.…”
Section: Immediate Survival Focusmentioning
confidence: 99%
“…Finally, two other mnemonic processes are related to the OB. The first consists of the tendency of smokers to recall positive smoking-related information more easily such as hedonistic pleasure, cognitive enhancement, and stress reduction compared to negative smoking-related information, such as coughing and disease (67). This attitude could be partially explained by another cognitive mechanism, called positive bias.…”
Section: Psycho-cognitive Modulators In Smoking Continuance Cessatiomentioning
confidence: 99%